PENINGKATAN HASIL BELAJAR MATERI TEKS NONFIKSI MELALUI MEDIA PEMBELAJARAN PAPAN PINTAR PADA SISWA KELAS V SDN BLURU KIDUL 2 SIDOARJO - Sarah Ramdhania; Ruri Fadhilah Kurniati; Fajar Nur Yasin (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2023)
This study aims to develop a learning media, namely a smart board. This learning media is highly recommended to be implemented in both low and high grades of elementary schools. This study applies qualitative research since it focuses on in-depth observation. Therefore, the use of qualitative methods in research can produce a more comprehensive study of a phenomenon. Data collection techniques used are interviews, tests, and observations. The validation results obtained were 96.15% which means that the smart board learning media can be applied. Based on the results of the data that have been obtained, it can be concluded that the knowledge or cognitive abilities of fifth grade students at SDN Bluru Kidul 2 Sidoarjo increased with the application of smart board learning media. In other words, the actions carried out in the study were said to be successful without any further action